Emotionally Intelligent Leadership at 30 Rock: What Librarians Can Learn from a Case Study of Comedy Writers. Issue 4 (18th May 2016) - Martin, Jason
ABSTRACT: Emotional intelligence is the ability to manage one's own and others' emotions and build relationships with people. Emotionally intelligent leadership is more and more important in today's ever-changing organizations like libraries. This article uses Goleman's five-point framework of emotional intelligence (self-awareness, self-regulation, motivation, empathy, and social skills) to analyze the leadership in the comedy sitcom 30 Rock and critique the importance of emotional intelligence in leadership.